Dziecko w katastrofie klimatycznej – świadek, ofiara, aktywista - Figura, Małgorzata (Paidia i Literatura, 2022)
Małgorzata Figura’s article is an attempt to capture the social roles of children when faced with the threat of the impending climate catastrophe. The introduction aims to draw attention to the need to give the floor to young people who can alert the public to changes taking place in the world. This necessity is stressed by researchers who represent children’s studies and who emphasize the importance of children’s perspective in literature and in scientific and social discourses. Figura’s analysis of selected literary texts allows us to see this turn towards the child, which at the same time is also the child’s turn towards nature.